Procedure utilization, latency and mortality: Weekend versus Weekday admission for Myocardial Infarction - Makki, Nader; Kline, David M; Kanmanthareddy, Arun; Mathelier, Hansie; Shreenivas, Satya; Lilly, Scott M (Journal of Cardiology and Cardiovascular Medicine, 2017)
Background: Due to variations in hospital protocols and personnel availability, individuals with myocardial infarction admitted on the weekend may be less likely to receive invasive procedures, or may receive them with a greater latency than those admitted during the week. Whether or not this occurs, and translates into a difference in outcomes is not established. Method: Using the Nationwide Inpatient Sample (2008-2011) database, we identified all patients admitted with a principle diagnosis of acute myocardial infarction. They were stratified by weekend or weekday admission. Baseline clinical characteristics, procedure utilization and latency to procedure were compared, and logistic regression models were constructed to assess the relationship between these variables and in-hospital mortality. Results: Patient demographics and provider-related characteristics (hospital type, geography) were similar between weekend and weekday admission for myocardial infarction. Adjusted for covariates, we found that the odds of mortality for a weekend admission are 5% greater than for a weekday admission (OR: 1.05; 95% CI: 1.01, 1.09, p=0.009). For the utilization of an invasive procedure, we found that the odds of receiving a procedure for a weekend admission were 12% less than the odds for a weekday admission, adjusted for the other covariates (OR: 0.88; 95% CI: 0.86, 0.91, p<0.001). In addition, we found that the time to procedure was an average of 0.18 days (4.32 hours) longer for weekend admissions compared to weekday admissions (95% CI: 0.16, 0.20, p<0.001). However, we did not observe a significant difference in the overall length of stay for weekend and weekday admissions (0.004 days; 95% CI: -0.04, 0.05, p=0.87). Conclusion: In a large and diverse subset of patients admitted with myocardial infarction, weekend admission was associated with fewer procedures, increased latency to those procedures, and a non-significant trend towards greater in adjusted in-hospital mortality.